Α-Linolenic acid regulates macrophages via GPR120-NLRP3 inflammasome pathway to ameliorate diabetic rats. (December 2022) - Liu, Yuanyuan; Guo, Mixue; Li, Yiwei; Wang, Ting; Ren, Yi; Wang, Rui; Jiang, Xin; Zhang, Xiaoxia; Tian, Jianying; Wang, Hao
Graphical abstract: Highlights: The mechanism of ALA ameliorating T2DM was comprehensively elucidated. GPR120-NLRP3 acts as a control point of anti-inflammatory and controlling glucose. ALA mainly ameliorated chronic inflammation via stimulating GPR120-NLRP3 pathway. ALA potentially served as an inexpensive, safe, effective intervention for T2DM. Abstract: Type 2 diabetes mellitus (T2DM) is closely associated with chronic low-grade inflammation. Accumulating evidences suggest that GPR120 activation and NLRP3 inflammasome suppression contribute to ameliorate chronic inflammation. α-linolenic acid (ALA) has been proved to be beneficial in chronic metabolic diseases. However, the triggering mechanisms of ALA alleviated the inflammation in T2DM by GPR120-NLRP3 inflammasome pathway are still poorly understood. The present study was designed as two phase: in vivo, the levels of FBG, HbA1c, liver macrophages and NLRP3 inflammasome components were significantly attenuated with ALA intervention; in vitro, ALA inhibited the expression of NLRP3 inflammasome complex and the activation of NF-κB, enhanced GPR120 and subsequent β-arrestin2 in LPS-stimulated RAW264.7 cells. Intriguingly, blocked with GPR120 antagonist AH7614, the inhibitory effects of ALA on NLRP3 inflammasome and TLR4/NF-κB pathway activity were weakened. Collectively, these results indicated that ALA regulated macrophages by GPR120-NLRP3 pathway to ameliorate T2DM.